Contagion, a Futurist South African Climate Crisis and a Hidden Drug Pandemic in Mohale Mashigo’s Intruders: Short Stories - Manase, Irikidzayi (Journal of Literary Studies, 2022)
The article draws on typologies of contagion, particularly matrices and patterns of virality considered here as tropes from the Bakhtinian chronotope. Using this frame, it analyses how society attempts to control crises and contagions in Mohale Mashigo’s speculative stories, “Untitled i,” “Untitled ii,” and “Ghost Strain N.” The Foucauldian notion of heterotopic juxtaposition of spaces complements the trope of contagion in unpacking how Mashigo’s characters encounter their specific forms of disasters and epidemics in ways that conform to past mass contagions and also break with those. In its focus on continuities and discontinuities regarding typologies of epidemics and pandemics, the article considers Mashigo’s use of African science fiction and fantasy (speculative fiction) to depict the life experiences and flight from an unfolding climate disaster to another galaxy in “Untitled i” and “Untitled ii,” and the spread of a drug epidemic in a fictional Johannesburg township in “Ghost Strain N.” It argues that we can understand these stories by making heterotopic linkages with the present Covid-19 and various life-changing crises and infections that humanity has encountered, is facing right now and will encounter as it moves with time and strives for survival. Opsomming Hierdie artikel put uit tipologieë van besmetting—veral matrikse en patrone van virusverskynsels wat hier beskou word as stylfigure van die Bakhtiniese chronotoop. Met behulp van hierdie raamwerk ontleed dit hoe die samelewing probeer om krisisse en besmettings te beheer in Mashigo se spekulatiewe stories, “Untitled i,” Untitled ii” en “Ghost Strain N.” Die Foucauldiese gedagte van heterotopiese naasmekaarstelling van ruimtes komplementeer die stylfiguur van besmetting in die uitmekaarhaal van hoe Mashigo se karakters hul spesifieke vorme van rampe en epidemies teëkom op maniere wat voldoen aan—en ook breek met—massabesmettings uit die verlede. In die fokus daarvan op kontinuïteite en diskontinuïteite rakende topologieë van epidemies en pandemies, bestudeer die artikel Mashigo se gebruik van Afrika-wetenskapsfiksie en van fantasie (spekulatiewe fiksie) om die lewenservarings en vlug van 'n ontvouende klimaatramp na 'n ander sterrestelsel uit te beeld in “Untitled i” en “Untitled ii,” en die verspreiding van 'n dwelmepidemie in 'n fiktiewe Johannesburgse township in “Ghost Strain N.” Daar word beredeneer dat ons hierdie verhale kan verstaan deur heterotopiese verbande te bewerkstellig met die huidige Covid-19-situasie en verskeie lewensbedreigende krisisse en infeksies wat die mensdom tans in die gesig staar, in die verlede beleef het en sal teëkom namate dit met tyd beweeg en oorlewing nastreef.